(untitled) (Acta Polytechnica CTU Proceedings, 2019)
This paper presents an experimental verification of impregnated textile reinforcement splicing by overlapping using tensile test of small textile reinforced concrete slabs before its using in the product. The specimen dimensions were designed 80×360mm and thickness approximately 18 mm. This specimen was reinforced using two pieces of impregnated flat technical fabric from carbon roving and epoxy resin. Two overlap lengths were designed using data from previous cohesion tensile tests and necessary anchoring length. The purpose of this experiment was experimental verification before flat reinforcement splicing by overlapping on the final product – furniture with textile reinforcement. This paper shows possible problems and complications in the anchoring of the textile reinforcements and in splicing by overlapping, the importance of the accuracy reinforcement position in the thin concrete cross-sectional area.